Anarquismo em papel e tinta: imprensa, edição e cultura libertária (1945 - 1968) - Viana, Allyson Bruno (2014)
The thesis aims to investigate the presence of anarchism - its ideas and practices - in Brazil, between the end of the Estado Novo in 1945 and the enactment of the Institutional Act No. 5, in 1968. From a study of libertarians printed, especially press and books, we seek to scale their role as learning strategies and self-education interwoven into the broader project of disseminating libertarian culture. So the study falls within the field of book history, the printing and reading, where the central influence of analysis on the varied reading practices and their circulation, focusing on the experience of the anarchist movement in Brazil and discussing peculiarities of its reorganization after an dictatorship period as well as the attempting to public insertion in a moment of regaining formal political freedoms.